2010
DOI: 10.1080/15321811003617438
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of the Amdl-Elisa DR-70 (Fdp) Assay Over Carcinoembryonic Antigen (Cea) for Monitoring Colorectal Cancer Patients

Abstract: The DR-70® (FDP) test was the first cancer test cleared by USFDA for monitoring colorectal cancer (CRC) since Carcinoembryonic Antigen (CEA) in 1982. Conservatively, 50% of biopsy-positive CRC patients have negative CEA values. DR-70 and CEA values were compared for 113 CRC monitoring patients. Total concordance rates for DR-70 and CEA were 0.665 and 0.686, respectively. CRC patient pairs were grouped based on their CEA value to deduce DR-70's effectiveness at monitoring patients with low CEA values. DR-70 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 59 publications
0
17
0
3
Order By: Relevance
“…It is a proven fact that there is a clear relation between increased FDP levels and cancer detection, its stage, progression and prognosis (7)(8)(9). DR-70 analysis has been previously stated to be effective in the detection of malignancies related with nasopharynx, tongue, gastrointestinal system, breast, ovarium and prostate (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a proven fact that there is a clear relation between increased FDP levels and cancer detection, its stage, progression and prognosis (7)(8)(9). DR-70 analysis has been previously stated to be effective in the detection of malignancies related with nasopharynx, tongue, gastrointestinal system, breast, ovarium and prostate (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…DR-70 analysis has been previously stated to be effective in the detection of malignancies related with nasopharynx, tongue, gastrointestinal system, breast, ovarium and prostate (10)(11)(12).…”
Section: Amdl-elisa Dr-70 (Fdp) Test Is the First In Vitro Diagnosticmentioning
confidence: 99%
“…Ayrıca bu antijenin sağlıklı organlarda; karaciğer, akciğer ve gastrointestinal sistemde benign durumlara bağlı olarak da seviyesinin arttığı bilinmektedir. 3 Yapılan çalışmalarda; kanser varlığı ile fibrin ve fibrin yıkım ürünlerinin arasında güçlü bir ilişki olduğu gösterilmiştir. Bahsedilen bu tümörlerin prokaogülan ve fibrinolitik faktörleri salgıladığı ve bunun sonucunda, ekstrensek koagülasyon sistemi ve fibrinolitik sistemin aktive olduğu gösterilmiştir.…”
unclassified
“…AMDL-ELISA DR-70 testi, 1982'de CEA'nın kolorektal kanser izleminde FDA onayından sonra, ruhsat alan ilk in vitro kanser tanı testidir. 3 Biz bu çalışmada; kolonoskopi yapılarak kolon kanseri tanısı almış hastalarda serum CEA ve DR-70 düzeyleri ile kanserin pTNM evresi arasında ilişki olup olmadığını, hem ayrı ayrı hem de her ikisini birlikte değerlendirerek ortaya koymaya ça-lıştık. …”
unclassified
“…Although the DR-70 immunoassay has been reported to be clinically sensitive for the detection of several malignancies (9,12,(17)(18)(19)(20)(21)(22)(23), extremely few studies have investigated the clinical efficiency of DR-70 for the detection of lung cancer. A number of studies have demonstrated that hemostatic alterations are frequently observed in lung cancer patients and the degree of coagulation and fibrinolysis activation has been correlated with the clinical progression of the disease (5,24,25).…”
Section: Introductionmentioning
confidence: 99%